Treatment of Delta Hepatitis: Today and in the Future - A review - Bahcecioglu, Ibrahim Halil; Sahin, Abdurrahman (Taylor & Francis Ltd, 2017)
Hepatitis delta virus (HDV) is a defective satellite virus and propagates in the presence of Hepatitis B virus (HBV) surface antigen (HBsAg). Approximately 5% of the people who infected with HBV are also infected with HDV. Chronic hepatitis caused by delta is the most severe form of chronic viral hepatitis including accelerated fibrosis, liver decompensation and development of hepatocellular carcinoma. Interferon-based therapies still remain the only treatment option of the hepatitis delta. The beneficiary effects of the interferon-based therapies, however, stop frequently with termination of the given therapy and relapse rate is very high. Accordingly, the efficiency rate of this treatment does not exceed 30%. On the other hand, serious side effects of interferons are another troublesome leading to withdrawal of the therapy. The main goal of the current treatments is clearance of HBsAg. There is no available drug acting directly against the HDV. New therapies interacting with HDV life cycle are under investigation. While prenylation inhibitors act on merely HDV, viral entry inhibitors and HBsAg release inhibitors would be used in the treatment of both HBV and HDV. We hope that in the future, the use of novel therapies and HBV vaccination provide to clinicians to cope with this troublesome agent.
Keywords: Hepatitis delta; conventional interferon; pegylated interferon; nucleoside/nucleotide analogues; prenylation inhibitor; viral entry inhibitor